1990
DOI: 10.1002/nme.1620290409
|View full text |Cite
|
Sign up to set email alerts
|

Improved hybrid solid element with a traction‐free cylindrical surface

Abstract: SUMMARYNew 8-node solid elements with two parallel faces and one traction-free cylindrical surface are derived using the assumed stress hybrid model. Six new expressions of stress components are developed by using four stress functions and cylindrical co-ordinates, so that the normal stress 0, on the plane perpendicular to the two parallel faces varies as a parabola, and the assumed stress field satisfies the equilibrium equations as well as the traction-free conditions over the cylindrical boundary. The assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In the following, two different strategies for selecting the higher-order interpolation are examined. The first consists of introducing additional nodes, and in particular midside nodes, as suggested in References [7,8] for three-dimensional elements and in References [11][12][13][14][15][16][17][18][19] for plane elements. The second consists of introducing additional drilling degrees of freedom in the existing corner nodes, as proposed in Reference [11].…”
Section: Displacement Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following, two different strategies for selecting the higher-order interpolation are examined. The first consists of introducing additional nodes, and in particular midside nodes, as suggested in References [7,8] for three-dimensional elements and in References [11][12][13][14][15][16][17][18][19] for plane elements. The second consists of introducing additional drilling degrees of freedom in the existing corner nodes, as proposed in Reference [11].…”
Section: Displacement Approximationmentioning
confidence: 99%
“…In fact, it has been found that the stress distributions obtained by enforcing the traction-free condition a posteriori may be inaccurate [6]. On the contrary, special mixed finite elements based on assumed stresses which obey a priori the condition of vanishing for tractions on the cavity rim have been successfully applied to various problems, such as for example biand three-dimensional elasticity [6][7][8][9][10][11][12], fracture mechanics [13][14][15][16][17] and coupled deformationdiffusion [18,19]. Of course, such improvements are achieved only if a proper balance between the approximations assumed for static and kinematic variables is preserved as it always occurs for mixed models.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…where the matrices G and H are determined by equation (11). In the following numerical examples the sti ness matrices k of these kinds of element are calculated by using the simple equation (13).…”
Section: Element Stiffness Matricesmentioning
confidence: 99%
“…In general, the convergence rate for the ÿnite element method is dominated by the nature of the solution in the vicinity of steep stress gradient. The regular high-accuracy element obtained by using polynomials of high order as interpolating functions cannot improve the rate of convergence [19][20][21]. So, more computational di culty is encountered for the small aspect ratios for the free-edge problems.…”
Section: Introductionmentioning
confidence: 99%